2011
DOI: 10.1007/s10549-011-1735-4
|View full text |Cite
|
Sign up to set email alerts
|

Invasive lobular carcinoma: response to neoadjuvant letrozole therapy

Abstract: Invasive lobular cancer (ILC) responds poorly to neoadjuvant chemotherapy but appears to respond well to endocrine therapy. We examined the effectiveness of neoadjuvant letrozole in postmenopausal women (PMW) with estrogen receptor (ER)-rich ILC. PMW were considered for treatment with neoadjuvant letrozole if they had ER-rich, large operable, or locally advanced cancers, or were unfit for surgical therapy. Tumor volume was estimated at diagnosis and at 3 months using calipers (clinical), ultrasound, and mammog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 33 publications
0
31
0
1
Order By: Relevance
“…ILC differs biologically and clinically from invasive ductal carcinoma (IDC). ILC occurs more often in older women, has increased incidence secondary to hormonal replacement therapy, tends to maintain hormone receptor signaling via estrogen receptor (ER) and progesterone receptor (PR), is often associated with lobular carcinoma in situ (LCIS), responds poorly to neoadjuvant chemotherapy, and metastasizes to unusual sites including the gynecologic and gastrointestinal tracts [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…ILC differs biologically and clinically from invasive ductal carcinoma (IDC). ILC occurs more often in older women, has increased incidence secondary to hormonal replacement therapy, tends to maintain hormone receptor signaling via estrogen receptor (ER) and progesterone receptor (PR), is often associated with lobular carcinoma in situ (LCIS), responds poorly to neoadjuvant chemotherapy, and metastasizes to unusual sites including the gynecologic and gastrointestinal tracts [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Inactivation of E-cadherin (CDH1) by a variety of molecular mechanisms is considered a defining characteristic of ILC. When compared with the more common invasive breast cancers of no special type, also known as invasive ductal carcinomas (IDC), ILC is more likely to be estrogen receptor-positive (ER þ ) and of lower nuclear grade (3). ILC is often large at diagnosis and there have been numerous reports on the response to neoadjuvant chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…It was thought that patients with ILC are significantly less likely to have a pathologic complete response than patients with IDC; however, a recent study concluded that ILC represents a heterogeneous group of tumors and the difference in response to neoadjuvant chemotherapy is largely explained by differences in molecular characteristics, particularly hormone receptor and HER2, and is independent of lobular histology (4). ILC have been shown to respond well to endocrine therapy (2) and we recently described the clinical response to neoadjuvant letrozole in a series of 61 patients (3). The lack of understanding of how lobular breast cancer responds to treatment is compounded by the paucity of research models (reviewed in ref.…”
Section: Introductionmentioning
confidence: 99%
“…Given the lower rates of pCR and high rates of ER positivity, some authors specifically suggest not to give chemotherapy for classic ILC, but instead to limit systemic treatment to endocrine manipulation in the neo‐adjuvant and adjuvant settings . In support of this, high rates of responsiveness to neo‐adjuvant letrozole therapy have been demonstrated . In a series of 61 postmenopausal patients with estrogen receptor positive ILC that were not eligible for BCS or who were deemed unfit for surgery, neo‐adjuvant letrozole therapy allowed for a clinical response or stable disease in 95% of the patients at 3 months.…”
Section: What Is the Optimal Methods Of Evaluation For Disease Extent mentioning
confidence: 99%